Cross-Country Spillovers of Fiscal Consolidations in the Euro Area - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2017)
This paper revisits the issue of cross-country spillovers from fiscal consolidations using an innovative empirical methodology. We find evidence in support of fiscal spillovers in 10 euro area countries. Fiscal consolidation in one country not only reduces domestic output (direct effect), but also the output of other member countries (indirect/spillover effect). Fiscal spillovers are larger for: (i) more closely located and economically integrated countries, and (ii) fiscal shocks originating from relatively larger countries. On average, 1 percent of GDP fiscal consolidation in 10 euro area countries reduces the combined output by 0.6 percent on impact, out of which half is driven by indirect effects from fiscal spillovers. The impact peters out and becomes insignificant over the medium-term. It is largely driven by tax measures, which have a relatively stronger effect on output compared to expenditure measures. The results are robust to alternative measures of bilateral links across countries.